USING ANIMATED VIDEO MEDIA AS PREVENTIVE STRATEGY TO REDUCE BULLYING AMONG STUDENTS IN SCHOOL SETTINGS - Ferry Andrian; Wisma, Nur; Saputro, Nurwahid Dimas; Dinata, Donaniagara (Jurusan Bimbingan dan Konseling, 2025)
Bullying is a serious problem in education that has a negative impact on students' psychological and social well-being. This study examines the effectiveness of animated videos in classical guidance services as a strategy to prevent bullying at SMA Muhammadiyah 1 Palembang. Using a one-group pretest-posttest experimental design on 37 students of grade XI 6, the instrument used was a validated Guttman scale test. Data analysis through paired sample t-test and N-Gain showed an increase in students' understanding from a pretest score of 51.76 to 84.05 in the posttest. The increase in N-Gain of 66% is quite effective. These results indicate that animated video media is effectively used in classical guidance services to increase students' awareness and understanding of bullying.